PENCAPAIAN KEPUASAN KERJA MELALUI PENILAIAN KINERJA KARYAWAN DAN EFIKASI DIRI PADA KOPERASI PT INDUSTRI TELEKOMUNIKASI INDONESIA BANDUNG - Muriawan, R. Suyudi; Sandewi, Risan (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2019)
Economic development affects the increasingly difficult society, all activities in an organization or from the company one of them is to manage its employees, job satisfaction is one thing that is closely related to employees. Job satisfaction can be measured through self-efficacy and employee performance Assessment. The purpose of this study to find out how much influence Employee Performance Assessment of job satisfaction at Cooperative Inti Bandung and how much influence self-efficacy on job satisfaction at Cooperative of PT Inti Bandung. The method of analysis in this study using descriptive and verification analysis. Unit in this research is employees of Cooperative Inti which amounted to 31 respondents as population. The sampling technique used in this research is saturated or census sampling so that the number of samples in this study were 31 respondents from the total population of employees. Data collection techniques through questionnaires, interviews and observations. The method of analysis using multiple linear regression analysis with partial hypothesis testing using T and simultaneous test using F test. Based on the results of descriptive research that shows that the assessment of employee performance on the category is very good enough, and self-efficacy is good enough, and job satisfaction is satisfactory. The result of verification research stated that job satisfaction can be determined by employee performance assessment and self-efficacy. In addition, the coefficient analysis of self-efficacy determination more influence on job satisfaction in comparison with the assessment of employee performance in Cooperative Inti Bandung.